(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Microtia-anotia has a global prevalence of 2.6 per 10,000 live births. Children with microtia-anotia will have an associated anomaly or an identifiable syndrome pattern in 20–60% of cases.1 The most common anomalies are facial cleft, facial asymmetry, renal abnormalities, cardiac defects, microphthalmia, polydactyly, and vertebral anomalies. Methods: This series consists of retrospective study of 30 patients who presented to the department of ENT, KEM Hospital between January 2010 to June 2013. Case Records of patients with congenital external ear deformity who presented to the E.N.T. Department during the time period from January 2010 to June 2013 were reviewed for the grade of microtia. The patients were also evaluated for associated congenital anomalies. Results: Associated anomalies in patients included facial paralysis, unilateral renal agenesis, congenital heart diseases, Cleft palate, microphthalmia, microcornea, iris coloboma, hemivertebra. Also Goldenhar syndrome / Hemifacial microsomia, Treacher- Collin syndrome and Pierre- Robin syndrome were the related syndromes to congenital external ear deformity in our series. Conclusion: Congenital external deformities may be associated with spectrum of other anomalies and the patient should receive best coordinated care from otolaryngologists, audiologists, paediatricians, heart specialist to improve the quality of life. Early hearing assessment should be followed by proper rehabilitation for adequate speech and language development. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 78-83